2005
DOI: 10.1007/s00167-005-0648-3
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularisation in chronic tendon injuries detected with colour Doppler ultrasound in horse and man: implications for research and treatment

Abstract: Recent research on chronic painful Achilles tendons in humans using ultrasonography and immunohistochemistry, has demonstrated an association between neurovascular ingrowth and tendon pain. In horses, chronic debilitating tendon conditions are well-known to be very difficult to treat, and the background to impaired function and pain is not scientifically clarified. In a collaborative research project between the Sports Medicine Unit in Umeå and Strömsholm Equine Hospital, grey-scale ultrasonography (US) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 21 publications
4
49
0
4
Order By: Relevance
“…Furthermore, the lesion-related loss of echogenicity has to be assigned correctly as being either a hematoma, edema or granulation tissue or whether these areas represent the physiological embedded muscle-fat-bundles (Nagy und Dyson 2012, Werpy et al 2012, Werpy et al 2013. Doppler ultrasonography may distinguish between different stages of highly vascularized granulation tissue in non-cadaver limbs (Kristoffersen et al 2005). MRI allowed visualization of a unilateral involvement of the muscle-fat-bundle in the morphological destruction of the PSL, the thickening of the dorsal fibrous part of the medial lobe and the thickening of the medial and palmar cortex of the third metacarpal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lesion-related loss of echogenicity has to be assigned correctly as being either a hematoma, edema or granulation tissue or whether these areas represent the physiological embedded muscle-fat-bundles (Nagy und Dyson 2012, Werpy et al 2012, Werpy et al 2013. Doppler ultrasonography may distinguish between different stages of highly vascularized granulation tissue in non-cadaver limbs (Kristoffersen et al 2005). MRI allowed visualization of a unilateral involvement of the muscle-fat-bundle in the morphological destruction of the PSL, the thickening of the dorsal fibrous part of the medial lobe and the thickening of the medial and palmar cortex of the third metacarpal bone.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus that normal equine tendons present no detectable intratendinous blood flow when evaluated with color or power Doppler ultrasound (Bosch et al 2011, Kristoffersen et al 2005. The role of persistent intra-tendinous vascularization is seen controversial in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The role of persistent intra-tendinous vascularization is seen controversial in the literature. Traditionally, persistent vascularization has been interpreted as a sign of inadequate healing and incomplete repair (Kristoffersen et al 2005, Murata et al 2012), but it is not clear in the literature for how many months the vascularization should be visible, so that it can be called persistent. On the contrary, Bosch and others (2011a) reported that 23 weeks after intra-tendinous PRP treatment, the PRP treated tendons presented a higher CDU vascularization score than saline treated tendons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The Achilles tendon and paratendon microcirculation in healthy athletes differ from patients with either insertional or mid-portion tendinopathy, where capillary blood flow at the point of pain is increased, as determined by laser Doppler flowmetry. 5 In a previous study, using a non-invasive real-time laser Doppler spectrophotometry system on the ankle to detect the microcirculatory effects of combined cryotherapy and compression as achieved by the AIRCAST Cryo/Cuff device (AIRCAST, Summit, NJ, USA), we found the relevant effects on microcirculation of combined cryotherapy and compression to take place within the first 10 min of application during a total 30 min application time.…”
mentioning
confidence: 99%